(untitled) - Natália Bolfarini Tognoli (Universidade Federal Fluminense - UFF, Brasil); Lu An (Wuhan University, China) (Deputy Editor); Thiago Barros (Federal University of Rio Grande do Sul, Brazil) (Managing Editor); Maja Žumer (University of Ljubljana, Slovenia) (Deputy Editor) (KO KNOWLEDGE ORGANIZATION, 2012)
KNOWLEDGE ORGANIZATION is a forum for all those interested in the organization of knowledge on a universal or a domain-specific scale, using concept-analytical or concept-synthetical approaches, as well as quantitative and qualitative methodologies. KNOWLEDGE ORGANIZATION also addresses the intellectual and automatic compilation and use of classification systems and thesauri in all fields of knowledge, with special attention being given to the problems of terminology.KNOWLEDGE ORGANIZATION publishes original articles, reports on conferences and similar communications, as well as book reviews, letters to the editor, and an extensive annotated bibliography of recent classification and indexing literature.KNOWLEDGE ORGANIZATION should therefore be available at every university and research library of every country, at every information center, at colleges and schools of library and information science, in the hands of everybody interested in the fields mentioned above and thus also at every office for updating information on any topic related to the problems of order in our information-flooded times.